ETIOPATHOGENIC ASPECTS OF ODONTOGENIC MAXILLARY SINUSITIS OF PERIAPICAL ORIGIN - Feijó-Alcântara, Ana Clara; Santos-Lima, Cleiton Rone; Veras-Diniz, Jade; Delgado-Souza, Júlia Veríssimo; Silva-Batista, Matheus Gabriel; Albuquerque-Melo, Rafaela Oliveira Cavalcanti; Araujo-Silva, Gabriel (Revista de Patologia do Tocantins, 2024)
Anatomically, the roots of the upper premolar and molar teeth are near the maxillary sinuses. Thus, periapical inflammation of the elements close to the sinuses enables the formation of odontogenic sinusitis. This study aimed to analyze the available literature on the etiopathogenic aspects of odontogenic maxillary sinusitis of periapical origin. A literature review was conducted in the following databases: SciELO, MEDLINE/Pubmed, and LILACS, using the keywords "Maxillary Sinusitis", "Dentistry", "Tooth" and "Infection". Articles written in English, Spanish, and Portuguese were included; those that fit the focus of the paper and those that were most relevant in terms of outlining the desired information. Papers reporting odontogenic sinusitis arising from an operative process were excluded. Odontogenic maxillary sinusitis (OMS) occurs due to sinus infection caused by inflammation of one or more dental elements near this cavity. Despite presenting specific features, sinusitis of odontogenic and non-odontogenic origin are quite similar, making the differential diagnosis difficult. Cone-Beam Computed Tomography (CBCT) is considered the reference standard for diagnosis, and the best treatment is to eliminate the causal factor. It was also found that apical periodontitis is the main non-iatrogenic cause and premolars and molars are the most affected teeth due to their anatomical location near the maxillary sinuses. The anatomical location of the maxillary sinus and the roots of the molars and premolars will allow, through the proximity between them, the OMS. In cases where periodontitis has proven to be the most frequent non-iatrogenic cause of this condition, also due to a great symptomatological similarity with non-odontogenic sinusitis, complementary examinations such as CBCT are necessary. Moreover, the treatment can be performed in a case-specific manner, through accurate diagnosis and etiopathogenesis.